(untitled) (ABDIMAS: Jurnal Pengabdian Masyarakat, 2022)
This service aims to assist assistance in implementing SECAR (Ceria Ceria) ABK based on Fundamental Movement for Down syndrome children to improve the fundamental movement of Down syndrome students at the Tunas Harapan Special School, Karawang. This is because the downsyndromic children at the Tunas Harapan Karawang Special School have poor basic movement skills. And through this gymnastic activity accompanied by cheerful and fun music to further attract students’ interest in following the gymnastics movements. This exercise consists of warm-up movements, core movements, and cool-down movements. The method used in this community service is a personal approach starting with personal introductions, doing activities outside the classroom, creating SECAR (cheerful gymnastics) for ABK Based on Fundamental Movement, and inviting students to demonstrate. In its implementation, SECAR (cheerful gymnastics) for ABK based on the fundamental movement at SLB Tunas Harapan Karawang, students are very enthusiastic about participating in the SECAR movement. While the obstacles faced are 1) students are difficult to control when doing gymnastics, 2) one student must be accompanied by a companion to correct his movements, and 3) the short implementation time makes it difficult for students to repeat the movement. The methods used in this training are counseling, discussion and training. And the training participants were given a conceptual understanding of the SECAR (cheerful exercise) for ABK based on the Fundamental Movement and at the same time they practiced the SECAR (cheerful exercise) movement based on the Fundamental Movement. This training has succeeded in achieving its goal of increasing the basic movement / Fundamental Movement for downsyndromic children at the Tunas Harapan Special School. Karawang.